FILFIL SIYAH (PIPER NIGRUM L.): AN INCREDIBLE MEDICINAL SPICE IN UNANI SYSTEM OF MEDICINE - SHAISTA BANO; MD SHAFAT KARIM; MD KAUSAR ALI (The Bioscan, 2025)
Black pepper (Piper nigrum L.), commonly referred to as Filfil Siyah in Unani medicine, is one of the most widely consumed spices worldwide. Beyond its culinary importance, it has been traditionally employed in several systems of medicine, including those practiced in India and China, for a wide range of ailments. Therapeutically, it has been used for the management of conditions such as fever, indigestion, flatulence, toothache, common cold, cough, asthma, and hemorrhoids. The present review aims to systematically compile and discuss the available information on Piper nigrum L., covering its introduction, geographical distribution, macro- and microscopic characteristics, temperament (Mizaj), phytochemical composition, therapeutic actions, toxicity profile, corrective agents (Musleh), formulations in which it is used, and evidence from modern pharmacological investigations. Filfil Siyah (Piper nigrum L.) exhibits a broad spectrum of pharmacological activities, including anti-inflammatory, antioxidant, anticancer, neuroprotective, antimicrobial, and antidepressant effects. Its major bioactive alkaloids comprise piperine, chavicine, piperidine, and piperetine. The present review consolidates traditional knowledge and recent scientific findings on Piper nigrum, with a focus on its phytochemistry and therapeutic potential. This compilation is expected to serve as a valuable reference for future investigations aimed at isolating active constituents and exploring their pharmacological mechanisms.